The DIFUSI INOVASI PROGRAM MASYARAKAT PEDULI TB TANJUNG GADANG (MASPETTAG) DI PUSKESMAS TANJUNG GADANG KABUPATEN SIJUNJUNG: DIFUSI INOVASI PROGRAM MASYARAKAT PEDULI TB TANJUNG GADANG (MASPETTAG) DI PUSKESMAS TANJUNG GADANG KABUPATEN SIJUNJUNG - septia refni darmisa (Jurnal Administrasi Publik dan Pemerintahan, 2023)
The aim of study to describe the diffusion of innovations in the Tanjung Gadang TB Care Community (Maspettag) program at the Tanjung Gadang Health Center, Sijunjung Regency. The background of this research is about health problems, one of which is TB disease or commonly known as Tuberculosis. The study used M. Rogers's theory of innovation diffusion with four variables including the innovation, communication channels, time, and a social system. The method used in this research is descriptive qualitative. Data collection techniques were carried out by interviews and documentation. Selection of informants using purposive sampling technique. Data analysis was carried out by grouping data, reducing data, presenting data, and drawing conclusions. For the validity of the data using source triangulation. The results of this study indicate that the innovation diffusion of the Tanjung Gadang TB Care Community (Maspettag) program has been going well. This can be seen from the innovation of the Maspettag program that has met the indicators of the theory of diffusion of innovation. Although there are still obstacles experienced by cadres when they go to the field due to rejection from the community. The innovation communication channel section, the Maspettag program does not use social media and only uses interpersonal channels to spread innovation to the public. The time variable for the spread of innovation is quite fast, it can be seen from the increasing number of suspected TB discoveries. Finally, the social system variable of the Maspettag program innovation fulfill indicators of the social system